Harm reduction and e-cigarettes: Distorting the approach. - Moore, M.; McKee, M.; Daube, Mike (2016)
Some supporters of electronic cigarettes have argued that they should be considered a form of harm reduction, analogous to that which has been successful with narcotics. In this viewpoint, we contend that this argument is based on highly selective use of the evidence, coupled with a fundamental misunderstanding of a comprehensive harm minimisation strategy. This includes not only harm reduction but also reduction in demand and supply-two elements that are explicitly rejected by many advocates of electronic cigarettes. We contend that, in the absence of all three elements, there is a danger that electronic cigarettes will delay the achievement of a tobacco-free world.